Effects of Insulin on Porcine Neonatal Sertoli Cell Responsiveness to FSH In Vitro - Rossella Cannarella (Journal of Clinical Medicine, 2019)
There is ongoing debate as to whether the decline of sperm production in recent times may be related to a parallel increase in the rate of obesity and diabetes. Lower anti-Müllerian hormone (AMH) and inhibin B secretion have been observed in young hyperinsulinemic patients compared to healthy controls, suggesting a Sertoli cell (SC) dysfunction. The pathophysiological mechanisms underlying SC dysfunction in these patients are poorly understood. To the best of our knowledge, no evidence is available on the effects of insulin on SC function. Therefore, this study was undertaken to assess the effects of insulin on basal and follicle-stimulating hormone (FSH)-stimulated SC function in vitro. To accomplish this, we evaluated the expression of AMH, inhibin B and FSHR genes, the secretion of AMH and inhibin B and the phosphorylation of AKT473 and SC proliferation on neonatal porcine SC after incubation with FSH and/or insulin. We found that similar to FSH, the expression and secretion of AMH is suppressed by insulin. Co-incubation with FSH and insulin decreased AMH secretion significantly more than with FSH alone. Insulin had no effect on the expression and secretion of the inhibin B gene, but co-incubation with FSH and insulin had a lower effect on inhibin B secretion than that found with FSH alone. FSH and/or insulin increased AKT473 phosphorylation and SC proliferation. In conclusion, the results of this study showed that insulin modulates SC function. We hypothesize that hyperinsulinemia may therefore influence testicular function even before puberty begins. Therefore, particular care should be taken to avoid the onset of hyperinsulinemia in children to prevent a future deleterious effect on fertility.